Inferior Alveolar Nerve Paresthesia Caused by a Dentigerous Cyst Associated with Three Teeth - Sümer, M.; Baş, B.; Yildiz, L. (My University, 2007)
The dentigerous cyst is a common pathologic entity associated with an impacted tooth, usually third molars. They generally are asymptomatic, being found on routine dental radiographic examination. This report describes the case of a 43 year old male with a large dentigerous cyst associated with mandibular canine, first and second premolar teeth that caused paresthesia of the inferior alveolar nerve. © Medicina Oral.
Keywords: Dentigerous Cyst; Inferior Alveolar Nerve Paresthesia; Mandible